Bantahan Ibnu Rusyd Terhadap Kritik Al-Ghazâlî Tentang Keqadiman Alam - Nurul Hidayat (Ulumuna, 2007)
Among “excess” of Muslims philosophers and teologians of middle ages were their ability to formulate divine teaching in speculative idea. That is true in the case of debate between al-Ghazali, deputizing theologians, with Ibnu Rusyd, deputizing philosophers. The debate was focused at problems how to comprehend creation of nature, whether it is creatio ex nihilo or creatio nihilo. The “victory” of al-Ghazali against philosophers took vital and important influence to growth of philosophy in Islam world. Being accused as infidel by al-Ghazali Muslims philosophers and philosophy was marginalized from Islamic treasures. Its impact admit of to be felt hitherto, that is in the form of ban, at least, suspicion to philosophy as science to mislead. To position both Islamic treasures—theology and philosophy—proportionally it is necessary to trace the debate between two disciplines since in fact the opinion of philosophers does not oppose against al-Qur'an, but against al-Ghazali’s opinion.